INDEKS DAYA SAING DAN FAKTOR - FAKTOR YANG MEMENGARUHI NILAI EKSPOR VANILI INDONESIA PERIODE 2004 – 2021 - Nur Hasanah; Darsono Darsono; Sri Marwanti (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2024)
Vanilla is one of the spices that has many benefits and a fantastic price. The high world demand for vanilla makes the competitiveness between exporters tighter. Each exporter tries to maintain the quality of their vanilla and the destination country market. In addition, other factors can affect vanilla exports from each exporter to the destination country. This study aims to determine the level of competitiveness and factors that affect the value of vanilla exports from Indonesia to destination countries. The method in this study uses ECI and panel data regression analysis. The results of the average ECI value show that vanilla from Indonesia has a strong competitiveness index in its export destination countries including China, India, the United States, the Netherlands and Thailand. This can be seen from the average value of ECI > 1. Factors that affect the value of Indonesian vanilla exports are the exchange rate of the rupiah against the United States dollar and the volume of Indonesian vanilla exports to destination countries which have a positive and significant effect. The population of the destination country and the GDP per capita of the destination country have a positive and insignificant effect. The covid 19 pandemic dummy has a negative and insignificant effect.